Feminist Strike: Liberia - Pamela Scully (Atlantis)
This paper examines the notion of feminist strike in reference to women peacemakers in Liberia. It argues that women's actions to bring an end to the war both instantiates normative notions of the feminist strike and expands them. Drawing on literature which points to a long history of Liberian women organizing as women with special roles and responsibilities in society, the paper invites us to adopt a broad understanding of the feminist strike. It also suggests that women's mobilization around the concept of a sex strike to force the end of war in the early 2000s, was a powerful and savvy move which criticised sexual violence in wartime, leveraged international attention, and also highlighted, if implicitly, the issue of sexual rights in marriage.